Descartes, according to the order of problems - Iván Dario, Iván Dario (Estudios de Filosofía, 1991)
The article intends to point out the relations between method, physics and metaphysics in Descartes. It is possible to say that, based on the fundamental idea of what science should be, Descartes conceives his physics and establishes mechanicism as the condition of all explanation and of all intelligibility; from this comes, as a result, the metaphysical consequences conceming the distinction between body and soul and the final topics regarding the union of the two that provide so much light to feelings and to morality